Adipose‐Derived Cell Construct Stabilizes Heart Function and Increases Microvascular Perfusion in an Established Infarct. (8th October 2013) - LeBlanc, Amanda J.; Nguyen, Quang T.; Touroo, Jeremy S.; Aird, Allison L.; Chang, Raymond C.; Ng, Chin K.; Hoying, James B.; Williams, Stuart K.
Abstract : This study investigated the cardiac recovery potential of a stromal vascular fraction (SVF) construct implanted onto an established infarct. Findings suggest that SVF treatment of an established infarct stabilizes the heart at the time point of intervention by preventing a worsening of cardiac performance and infarcted volume and increasing perfusion of the microcirculation. Abstract : We have previously shown that myocardial infarction (MI) immediately treated with an epicardial construct containing stromal vascular fraction (SVF) from adipose tissue preserved microvascular function and left ventricle contractile mechanisms. In order to evaluate a more clinically relevant condition, we investigated the cardiac recovery potential of an SVF construct implanted onto an established infarct. SVF cells were isolated from rat adipose tissue, plated on Vicryl, and cultured for 14 days. Fischer‐344 rats were separated into MI groups: (a) 6‐week MI (MI), (b) 6‐week MI treated with an SVF construct at 2 weeks (MI SVF), (c) 6‐week MI with Vicryl construct at 2 weeks (MI Vicryl), and (d) MI 2wk (time point of intervention). E max, an indicator of systolic performance and contractile function, was lower in the MI and MI Vicryl versus MI SVF. Positron emission tomography imaging ( 18 F‐fluorodeoxyglucose) revealed a decreased percentage of relative infarct volume in the MI SVF versus MI and MI Vicryl. Total vessel count and percentage of perfusion assessed via immunohistochemistry were both increased in the infarct region of MI SVF versus MI and MI Vicryl. Overall cardiac function, percentage of relative infarct, and percentage of perfusion were similar between MI SVF and MI 2wk; however, total vessel count increased after SVF treatment. These data suggest that SVF treatment of an established infarct stabilizes the heart at the time point of intervention by preventing a worsening of cardiac performance and infarcted volume, and is associated with increased microvessel perfusion in the area of established infarct.